2023
DOI: 10.1007/s40618-023-02050-2
|View full text |Cite
|
Sign up to set email alerts
|

High levels of LIGHT/TNFSF14 in patients with Prader–Willi syndrome

Abstract: Purpose/methods Prader–Willi syndrome (PWS) is a rare genetic disorder displaying different clinical features, including obesity and bone impairment. LIGHT/TNFSF14 is a cytokine produced by immune cells affecting both fat and bone metabolism. The present study aimed to evaluate LIGHT serum levels in 28 children and 52 adult PWS patients compared to age and sex-matched controls, as well as correlations with parameters of bone and fat metabolism. Results Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…The interest in exploring the role of LIGHT in HFD arises from the high levels of this cytokine detected in obesity, together with the conflicting results on the role of LIGHT in adipogenesis. The increased circulating levels of LIGHT have been demonstrated in obese pediatric and adult subjects, but also in genetic obesity associated with Prader-Willy patients [6][7][8]. Consistently, different murine models were used to study the role of LIGHT in obesity [13][14][15][16][17][18]24], and the complexity is also associated with the heterogeneous microenvironment that characterizes fat tissue.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The interest in exploring the role of LIGHT in HFD arises from the high levels of this cytokine detected in obesity, together with the conflicting results on the role of LIGHT in adipogenesis. The increased circulating levels of LIGHT have been demonstrated in obese pediatric and adult subjects, but also in genetic obesity associated with Prader-Willy patients [6][7][8]. Consistently, different murine models were used to study the role of LIGHT in obesity [13][14][15][16][17][18]24], and the complexity is also associated with the heterogeneous microenvironment that characterizes fat tissue.…”
Section: Discussionmentioning
confidence: 96%
“…However, with the primary objective of extending the use of this immunotherapy to other diseases, different studies have explored the role of LIGHT in metabolic diseases, including obesity. Previously published papers have reported an increase in circulating LIGHT levels in obese adults as well as in children [5,6], Prader Willi syndrome subjects displaying genetic obesity [7,8], and mice subjected to High Fat Diet (HFD composition: 19 MJ kg −1 , 35% of energy from carbohydrate, 42% from fat, 23% from protein) [9]. Conversely, an anti-inflammatory diet reduced systemic inflammation and thus LIGHT levels [10].…”
Section: Introductionmentioning
confidence: 99%
“…In obese individuals, serum levels of LIGHT correlate with reduced bone mineral density (Faienza et al, 2023). In cultures of peripheral blood mononuclear cells isolated from obese subjects, anti-LIGHT antibodies inhibit osteoclastogenesis .…”
Section: Discussionmentioning
confidence: 99%
“…LIGHT/TNFSF14 is a cytokine produced by immune cells that affects both fat and bone metabolism; Faienza et al showed that serum LIGHT levels were significantly higher in both PWS children and PWS adults than in controls (96). Additionally, LIGHT levels were found to have a negative correlation with DEXA parameters.…”
Section: Bone Metabolismmentioning
confidence: 99%